Optimization of fracturing parameters for horizontal wells in high-sulfur gas reservoirs considering the effect of sulfur deposition - Chang Sun; Zhongjun Zhao; Jinghong Hu; Yuan Zhang; Yidong Cai; Jun Lu (Petroleum Research)
During the development of high-sulfur gas reservoirs, the precipitation and deposition of elemental sulfur can lead to a reduction in reservoir porosity and permeability. Previous studies focus on the well production with optimized operational parameters, but the effect of sulfur deposition is not included, which impacts fracturing parameters, well production, and economic evaluation. Therefore, this work proposes a reasonable approach for parameter optimization considering sulfur. The variation of porosity and permeability are first evaluated during sulfur deposition. After that, fracture half-length, fracture spacing, fracture conductivity, and fracture distribution are optimized with orthogonalization factor analysis, and the influence of sulfur deposition on different fracture parameters are detailed analyzed. The results shown that the fracture half-length and fracture conductivity are greatly affected by sulfur deposition. Finally, net profit value is applied to obtain the optimal fracture spacing interval. With economic evaluation, the optimal fracture spacing interval of 125 m–150 m is determined considering the net profit and the payback period. This work provides a useful economic method for fracture parameter optimization high-sulfur gas reservoirs, which benefits for the development and production of gas reservoirs.